2017
DOI: 10.3892/etm.2017.4682
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal phenotypic features of IgM+B cell subsets in patients with chronic hepatitis C virus infection

Abstract: Abstract. Hepatitis C virus (HCV) infection is associated with B cell abnormality; however the phenotypic profiles of immunoglobulin (Ig)M+B cell subsets in patients with HCV infection remain unclear. In the current study, the effect of HCV infection on IgM+B cell subsets was evaluated. The percentages, as well as the differentiation and activation features of peripheral IgM+B naive subsets [cluster of differentiation (CD)27-IgM+B cells] and IgM+B memory subsets (CD27+IgM+B cells) were assessed using flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recently, a population of IgM + CD27 + memory B cells, were identified which can re-enter germinal center reactions and differentiate into antibody-secreting cells ( 61 63 ), however the generation and immune function of these cells is poorly understood. Kong et al ( 64 ) reported a higher frequency of this IgM + CD27 + memory B cell subset in chronic hepatitis C compared to healthy controls. Tucci et al ( 65 ) reported the presence of IgM + CD27 + B cell clones in chronic hepatitis C. Despite several attempts we were unable to isolate sufficient IgM + CD27 + B cells from our cohort of patients to demonstrate an enrichment of HCV RNA in this subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a population of IgM + CD27 + memory B cells, were identified which can re-enter germinal center reactions and differentiate into antibody-secreting cells ( 61 63 ), however the generation and immune function of these cells is poorly understood. Kong et al ( 64 ) reported a higher frequency of this IgM + CD27 + memory B cell subset in chronic hepatitis C compared to healthy controls. Tucci et al ( 65 ) reported the presence of IgM + CD27 + B cell clones in chronic hepatitis C. Despite several attempts we were unable to isolate sufficient IgM + CD27 + B cells from our cohort of patients to demonstrate an enrichment of HCV RNA in this subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“… 8 B1a cells are immunoglobulin M-positive B (IgM+ B) cells and involved in viral infection pathogenesis. 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 B1a cells are immunoglobulin M-positive B (IgM+ B) cells and involved in viral infection pathogenesis. 9 Even though the NKG2D receptor is not expressed in all B cell subsets, it has been observed that the absence of this receptor in hematological precursors affects peripheral B1a cell counts in cases of bacterial infections. 4 However, the association between host NKG2D receptor and B1a cell subsets in patients with HCV infection and its complications has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation